Suicide and Suicide Attempts Among Patients Attending Primary Health Care Facilities in Uganda: A Medical Records Review - Kaggwa MM; Rukundo GZ; Wakida EK; Maling S; Sserumaga BM; Atim LM; Obua C (Dove Medical Press, 2022)
Mark Mohan Kaggwa,1,2 Godfrey Zari Rukundo,1,2 Edith K Wakida,2- 4 Samuel Maling,1 Baker Makaya Sserumaga,1,2 Letizia Maria Atim,1,2 Celestino Obua5 1Department of Psychiatry, Mbarara University of Science and Technology, Mbarara, Uganda; 2African Centre for Suicide Prevention and Research, Mbarara, Uganda; 3Office of Research Administration, Mbarara University of Science and Technology, Mbarara, Uganda; 4Department of Medical Education, California University of Science and Medicine, San Barnardino, CA, United States of America; 5Department of Pharmacology and Therapeutics, Mbarara University of Science and Technology, Mbarara, UgandaCorrespondence: Mark Mohan Kaggwa, Email kmarkmohan@gmail.comBackground: Suicide is one of the leading causes of death globally, accounting for about 800,000 deaths annually. The suicide burden drastically increased since the beginning of the COVID-19 pandemic. In Uganda, no known study has determined the suicide rate since the beginning of the COVID-19 pandemic.Objective: To determine the suicide mortality rate and describe the characteristics of victims of suicide attempts from January to December 2020 in south western Uganda.Methods: This study was based on the health management information systems (HMIS) of patients' registered data for the year 2020 at 15 selected primary health care facilities in four districts in south-western Uganda. We used a data extraction tool to capture demographic and clinical characteristics of the individuals who had attempted or completed suicide. We estimated yearly incidence rates of fatal and non-fatal suicide attempts, and used chi-square and t-test to determine the statistical difference between suicide attempt outcomes.Results: A total of 130 non-fatal suicide attempts and 26 suicides were identified. Majority were male 69.87% (n = 109/156) and the mean age was 27.16 (SD = 14.71) years. The overall incidence of suicide attempts was about 60 attempts per 100,000 people, while that of completed suicide was about three deaths per 100,000 people. The suicide attempts increased following the first month of COVID-19 lockdown in the country (March 2020) and most individuals attempted suicide by poisoning (n = 144).Conclusion: Suicide is a common occurrence in primary health care settings of Uganda and there has been a rapid increase in suicide attempts since the onset of the COVID-19 pandemic. With suicide by poisoning being common, there is need for proactive interventions, such as the control of pesticides and herbicides, to prevent suicide among members of this community, especially during pandemic conditions.Keywords: suicide, non-fatal suicide attempt, suicide attempt, primary health care, COVID-19, pandemic, Uganda